Influence of waste plastic on pyrolysis of low-lipid microalgae: A study on thermokinetics, behaviors, evolved gas characteristics, and products distribution. (February 2022) - Kumar, Akash; Yan, Beibei; Tao, Junyu; Li, Jian; Kumari, Lata; Oba, Belay Tafa; Aborisade, Moses Akintayo; Chen, Guanyi
Abstract: In this study, co-pyrolysis of low-lipid Nannochloropsis sp. (NS) and waste polystyrene (PS) was deeply investigated using TG-MS-FTIR and Fixed bed reactor to characterize their thermal behaviors, kinetics, evolved gases, and products distribution. The (D)TG investigation of the co-pyrolysis process revealed two distinct stages of thermal decomposition: the first stage (150–420 °C) was mostly caused by NS decomposition, whereas the second stage (420–550 °C) was attributed to NS-PS decomposition. The difference between experimental and theoretical mass loss (ΔW) was lower than zero when the proportion of NS was 75% and 65%. In addition, the average activation energy of the blends containing 75% and 65% of NS was less than sole NS. Thus, based on thermal behaviors and activation energies, the blends with an NS content of 75% and 65% exhibited the strongest synergistic effect. The results of TG-MS, TG-FTIR, and GC-MS analyses revealed that the co-pyrolysis considerably boosted the production of hydrocarbons, notably aromatic hydrocarbons, while concurrently restricting the production of nitrogenous and oxygenous compounds. This study will contribute to a better understanding of the utilization of low-lipid microalgae. Graphical abstract: Image 1